Transcriptome immunomodulation of in-feed additives in Atlantic salmon Salmo salar infested with sea lice Caligus rogercresseyi - Núñez-Acuña, Gustavo; Goncalves, Ana Teresa; Valenzuela-Muñoz, Valentina; Pino-Marambio, Jorge; Wadsworth, Simón; Gallardo-Escárate, Cristian Jorge (Fish & Shellfish Immunology, 2021)
One of the most significant threats to the Chilean salmon aquaculture industry is the ectoparasitic sea louse caligus rogercresseyi. To cope with sea lice infestations, functional diets have become an important component in strengthening the host immune response. The aim of this study was to evaluate molecular mechanisms activated through immunostimulation by in-feed plant-derived additives in Atlantic salmon infected with sea lice. Herein, a transcriptome-wide sequencing analysis was performed from skin and head kidney tissues, evidencing that the immune response genes were the most variable after the challenge, especially in the head kidney, while other genes involved in metabolism were highly expressed individuals fed with the immunostimulants. Interestingly, defensive enzymes such as Cytochrome p450 and serpins were down-regulated in infested individuals, especially in skin tissue. Additionally, MHC-I and MHC-II genes were differentially expressed after the incorporation of the in-feed additives, giving some cues about the protection mechanisms of plant-derived compound as immunostimulants for infested salmons. This is the first published study that evaluates the transcriptomic response of sea lice-infested Atlantic salmon fed with in-feed additives. (c) 2015 Elsevier Ltd. All rights reserved. Regular 2015 FONDECYT FONDECYT